AN ANALYSIS OF DIFFICULTIES IN USING GERUND AND INFINITIVE FACED BY THE SIXTH SEMESTER STUDENTS OF ENGLISH STUDY PROGRAM OF UNIVERSITAS RIAU - Vonda Amelia; Novitri Novitri; Masyhur Masyhur (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2023)
Abstract: This research was conducted to analyze the difficulty level in using gerund and infinitive. The design of this research is descriptive quantitative. The participants of this study were 37 students that currently study in their sixth semester of English Study Program of Universitas Riau and they were selected by cluster random sampling. In collecting data, the researcher used a test. After getting the data, the researcher analyzed them to determine of students’ difficulty level in using gerund and infinitive. The result of data analysis showed the highest percentage of difficulty in using gerund and infinitive are gerund as a direct object 47% and to infinitive as an object, to infinitive as an adjective and bare infinitive after ‘would rather’ or ‘had better’ was 45%. In conclusion, to solve the difficulty part of gerund and infinitive there must be a way to solve them in the teaching of gerund and infinitive.Key Words: Difficulties, Gerund, Infinitive.